GROWTH AND PHOTOSYNTHETIC CO2 RESPONSES OF DATE PALM PLANTS TO WATER AVAILABILITY - Elshibli, Sakina; Elshibli, Elshibli Mohamed; Korpelainen, Helena (Emirates Journal of Food and Agriculture, 2017)
Date palm is known to survive and withstand harsh environment, especially under scarce water availability and extreme dry conditions. Drought adaptation in plant species includes evolutionary consequences detectable at a wide range of morphological, genetic as well as physiological multifunctional responses. Although, significant researches have been reported dealing with water relations of date palms to agronomic traits and yield performance, yet, revealing the mechanism of date palm adaptation to drought needs adequate attention. In this study, the aim was to examine the growth adjustments and photosynthetic CO2 (Carbon dioxide) responses of date palm plants to water availability. The experimental methodology included long-term irrigation treatments based on field capacity measures, evaluation of the biochemical gas exchange model and assessment of growth and photosynthetic performance. As results, a variety of morphological as well as physiological adjustments were observed to take place in response to water availability. Accelerated leaf senescence, reduced green area as well the balanced root: shoot ratio were among the main morphological adjustments observed. Stomatal conductance (gs) showed a slight decrease in response to increasing external supply of CO2 from ambient to 1,500 ppm (part per million), while intercellular CO2 (Ci) continued increasing up to the highest tested level. As consequences, the increasing CO2 significantly (P ≤ 0.001) increased the net photosynthetic rate of the intact leaves of date palm plants with significant (P ≤ 0.001) gas-water interaction effect. Reduction of water by 50% of field capacity did not generate significant effect on the photosynthetic ability of the tested plants; this result also confirmed by the slight changes in the biochemical reaction indices. However, at 25% and 10% water availability changes in responses become more pronounced. On the other hand, the reduction of gs by 30% at 10% water availability compared to 100% did not affect the increasing pattern of Ci/Ca ratio (intercellular CO2 concentration / gas external supply ratio) of elevated CO2 when compared to that of the ambient; an observation might indicate a non-absolute stomatal role among the determinants of photosynthetic capacity of date palms in response to water availability. The observed growth adjustments, the indexed changes in the photosynthetic biochemical reactions as well as the implications for date palm adaptation to drought are considered in the discussion.